Heterologous Production of Microbial Ribosomally Synthesized and Post-translationally Modified Peptides - Zhang, Yi; Chen, Manyun; Bruner, Steven D.; Ding, Yousong (Frontiers in Microbiology, 2018)
Ribosomally synthesized and post translationally modified peptides, or RiPPs, which have mainly isolated from microbes as well as plants, are an ever-expanding group of peptidic natural products with diverse chemical structures and biological activities. They have emerged as a major category of secondary metabolites partly due to a myriad of microbial genome sequencing endeavors and the availability of genome mining software in the past two decades. Heterologous expression of RiPP gene clusters mined from microbial genomes, which are often silent in native producers, in surrogate hosts such as Escherichia coli and Streptomyces strains can be an effective way to elucidate encoded peptides and produce novel derivatives. Emerging strategies have been developed to facilitate the success of the heterologous expression by targeting multiple synthetic biology levels, including individual proteins, pathways, metabolic flux and hosts. This review describes recent advances in heterologous production of RiPPs, mainly from microbes, with a focus on E. coli and Streptomyces strains as the surrogate hosts.